Gut microbiome and clinical and lifestyle host factors associated with recurrent positive RT-PCR for SARS-CoV-2 - Jiménez-Arroyo, Cristina; Molinero, Natalia; Sabater, Carlos; Margolles, Abelardo; Terrón-Camero, Laura Carmen; Andrés-León, Eduardo; Ramos, Manuel; del Val, Margarita; Moreno-Arribas, M. Victoria (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundSARS-CoV-2 and COVID-19 are still active in the population. Some patients remained PCR-positive for more than 4 weeks, called “persistently PCR-positive”. Recent evidence suggests a link between the gut microbiota and susceptibility to COVID-19, although no studies have explored persistent PCR conditions. We aimed to evaluate the relationship between persistent positive SARS-CoV-2 RT-PCR, the gut microbiome, and individual host determinants.MethodsA shotgun metagenomic analysis was conducted on fecal samples from 28 individuals affected by COVID-19. Patients were divided into two groups: those who had cleared the virus within 30 days (designated as the control group) (n = 15), and those who remained PCR-positive beyond 30 days (called the PCR+ group) (n = 13). We also investigated the correlation between prolonged viral clearance and several additional factors, including clinical parameters, immune responses, microbial metabolites, and dietary habits.ResultsThe composition and functionality of the microbiome varied based on the duration of positivity as determined by PCR. Compared to the control group, the persistent PCR+ group exhibited elevated pathogen levels and augmented diversity in functional gene families (p-value < 0.05). A multi-omics analysis integrating metagenomics, metabolites, and metadata also revealed the specific contribution of certain blood markers in this group, including basophils, IgM, IgG (both general and specific for SARS-CoV-2), and markers of liver damage. Unhealthy diet was identified as a significant factor influencing the duration of PCR positivity.ConclusionsThese findings indicate that the gut microbiome may play a role in delayed viral clearance and persistent positive RT-PCR results. Our study also contributes to the understanding of the role of host factors as mediators linking the gut microbiota and disease outcomes. Further large-scale studies must confirm these data; however, they suggest the relevance of monitoring microbiome changes in the early post-viral years to control SARS-CoV-2 and providing individual healthcare support.